DUKUNGAN NORWEGIA TERHADAP PERDAMAIAN DI MYANMAR: STUDI KASUS MYANMAR PEACE SUPPORT INITIATIVES (MPSI) - Jerry Indrawan (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2016)
Myanmar is well-known of its military junta and their prolonged conflicts. Nobel Peace Prize winner Aung San Suu Kyi has fought for Myanmar democracy since the late 1990’s. Unfortunately, the military put her in prison after his party winning the election in 1990. However, since constitutional change in 2008 and the general election in 2010 and 2012, Myanmar social and political condition has turned dramatically. Democracy has paved the way for Suu Kyi party to control the government, in such put Htin Kyaw as the first Myanmar President since the 1962 coup. As a result of this democratic condition, Norway support to Myanmar has increased significantly in the last few years. Support related to the promotion of democracy and emergency assistance has to be the focal point in this assistance. Peacemaking would be likely accepted if starts from democracy promotion efforts, including sending humanitarian assistance. Often, conflicts occur due to dissension among political elites, including the suffering of people experienced a shortage of daily needs because of the unresolved conflict. Norway main program in Myanmar is the Myanmar Peace Support Initiative (MPSI) program. MPSI is a program that aims to create peace in the regions that having ceasefires, such as Myanmar for instance. This article will explain a little about the historical-political conditions of Myanmar in the beginning. After that, the main focus of this paper is to explain what efforts are made by Norway in several fields in Myanmar to support the efforts for peace through MPSI. The main data in this paper obtained directly during the authors overseas course in Oslo, Norway in 2013, and also through an interview via e-mail to several parties in Norway that the authors consider competent.AbstrakNegara Myanmar dikenal dari junta militer dan konfliknya yang berkepanjangan. Pemenang hadiah Nobel Perdamaian Aung San Suu Kyi sejak akhir tahun 1990-an telah bertarung bagi demokrasi di Myanmar. Sayangnya, junta militer memasukkannya ke dalam penjara setelah partai yang dipimpinnya memenangi pemilihan umum tahun 1990. Akan tetapi, sejak perubahan konstitusi tahun 2008 dan pemilihan umum tahun 2010 dan 2012, kondisi sosial politik Myanmar berubah secara dramatis. Demokrasi telah melapangkan jalan bagi partai Suu Kyi untuk menguasai pemerintahan, dengan demikian menempatkan Htin Kyaw sebagai President sipil Myanmar pertama sejak kudeta tahun 1962. Sebagai akibat dari kondisi demokrasi Myanmar yang semakin membaik, dukungan Norwegia terhadap Myanmar meningkat secara signifikan sejak beberapa tahun terakhir. Dukungan terkait promosi terhadap demokrasi dan bantuan darurat di Myanmar menjadi fokus utama Norwegia. Upaya menuju perdamaian lebih memungkinkan untuk diterima apabila dimulai dari upaya-upaya promosi demokrasi, termasuk mengirimkan bantuan kemanusiaan. Terkadang, konflik terjadi karena pertikaian di antara para elit politik, termasuk penderitaan rakyat yang mengalami kekurangan bahan kebutuhan sehari-hari karena konflik yang tak terselesaikan. Program utama Norwegia di Myanmar adalah program Myanmar Peace Support Initiative (MPSI). MPSI adalah program yang bertujuan untuk menciptakan perdamaian di wilayah-wilayah yang sedang terjadi gencatan senjata, seperti di Myanmar. Pada awal tulisan ini akan dijelaskan sedikit tentang kondisi sejarah dan politik Myanmar. Setelah itu, fokus utama dari tulisan ini adalah untuk menjelaskan upaya-upaya apa saja yang dilakukan Norwegia, di dalam beberapa bidang di Myanmar, untuk mendukung perdamaian melalui MPSI. Data utama dalam tulisan ini didapatkan saat penulis melakukan kuliah kerja luar negeri di Oslo, Norwegia tahun 2013, serta melalui wawancara melalui email dengan beberapa pihak di Norwegia yang penulis anggap kompeten.